EXPERIMENTAL INVESTIGATION OF SPRINGBACK OF LOCALLY HEATED ADVANCED-HIGH STRENGTH STEELS - Eyercioglu, Omer; Alacaci, Sevket; Aladag, Mehmet (International Journal of Research -GRANTHAALAYAH, 2021)
Sheet metal bending is one of the important metals forming processes at ambient temperature. The usage of high-strength steel is one of the stronger materials for the construction of components in the automotive industries. However, for complex shapes, cold forming is not always sufficient, and heating the workpiece plays a major role in manufacturing these shapes. Bendability may increase with increasing forming temperature and currently, hot forming of advanced high strength steels (AHSS) is becoming more attractive. While hot forming of AHSS is beneficial for high formability, subsequent quenching is required to maintain final strength. This procedure extends the production time. In this study, temperature gradients, bending loads, and springback after V-bending were investigated. The experimental study was carried out on a 2 mm thick Docol 1500M steel at various temperatures by using a speed-controlled servo press machine. The bending regions of the specimens were locally heated to 200, 300, 400, 500, and 600oC by using a high-frequency induction heating device. The results show that; punch loads were significantly lowered with increasing the local heating temperature during bending. There were no cracks observed on the specimens. The amount of spring back is decreasing with the bending temperature and around 500oC almost no springback was measured. Negative spring back was observed for the bending temperatures higher than 500oC